The Use of Selected Linking Words in Academic Discourse - Zinkeová, Anežka (Univerzita Pardubice, 2023)
The main aim of this thesis is to analyse the different usage of selected linking words in two fields of academic discourse: philosophy and engineering scientific research articles. The theoretical part outlines the most typical features of academic writing and provides a detailed characterization of one of its major subtypes: the scientific research article. Furthermore, it describes in detail selected types of linking words, including linking adverbials and conjunctions, along with their selected semantic categories, with a particular focus on their specific linking words. The practical part aims to analyse the occurrence of such linking words while comparing their usage and frequency in the two selected genres.
Využití vybraných spojovacích slov v akademickém diskurzu
Keywords: academic discourse; scientific research article; linking words; linking adverbials; conjunctions; akademický diskurz; odborný vědecký článek; spojovací slova; spojovací příslovečná určení; spojky